Promoter hyper-methylation of calcium binding proteins S100A6 and S100A2 in human prostate cancer. - Rehman, I; Cross, S; Catto, J; Leiblich, A; Mukherjee, A; Azzouzi, A; Leung, H; Hamdy, F (2005)
BACKGROUND: S100A6 and S100A2 are members of the S100 family of calcium binding proteins, which are down regulated in prostate cancer, however the molecular mechanism(s) underlying their loss of expression is unknown. METHODS: The promoter and exon 1 region of the S100A6 and S100A2 genes was sequenced in bisulfite modified DNA from non-malignant, benign prostatic hyperplasia (BPH), malignant and metastatic prostate tissues and in cell lines. Immunohistochemistry was performed to correlate S100A2 expression with methylation status. RESULTS: S100A6 methylation was absent or occurred at isolated sites in 14/14 cases of non-malignant epithelium and 5/5 cases of BPH tissues, whereas methylation was seen in 14/27 (52%) cases of prostatic cancer (P<0.0001), 2/2 cases of metastatic cancer and in the CWR22 prostatic cancer xenograft. Critical CpG sites within the S100A2 promoter were methylated in LNCaP, LNCaP-LN3, and CWR22 cells but not in Du145, PC3 or BPH45 cells. In tissues, S100A2 methylation was seen in 32/34 (94%) cases of adenocarcinoma and 5/5 cases of metastatic cancer. However, S100A2 methylation was also seen in 9/12 (75%) cases of non-malignant tissues and in 5/5 cases of BPH. Immunostaining, showed absent S100A2 expression all 41 cases of prostatic cancer, whereas staining was seen in the basal cells of non-malignant epithelium. CONCLUSIONS: Loss of S100A6 and S100A2 proteins is frequent in human prostatic cancer. A major mechanism underlying the loss of S100A6 expression appears to involve promoter hyper-methylation. However, mechanisms other than methylation of the known promoter are involved in silencing S100A2 in the prostate.